2006
DOI: 10.1583/06-1849.1
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Buttock Claudication Following Stent-Graft Coverage of the Hypogastric Artery Without Coil Embolization in Endovascular Aneurysm Repair

Abstract: Stent-graft coverage of the orifice of the hypogastric artery without coil embolization is a safe and effective adjunct during the treatment of aortoiliac or iliac aneurysm, with a low incidence of buttock claudication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Previous studies on EVAR with IIA coverage for aortoiliac aneurysms applied a selective approach in deciding whether or not to embolise the IIA; Bharwani et al 22 and Farahmand et al 21 only included cases without coil embolisation in which attempted embolisation had technically failed or in which the IIA had been covered inadvertently. The group from the University of Wisconsin presented two reports on patients with and without coil embolisation, 24,25 but no reasons were provided for their decision whether or not to perform concomitant IIA embolisation. Wyers et al 23 decided not to embolise the IIA if a sealing zone of at least 5 mm was present in the most distal part of the CIA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on EVAR with IIA coverage for aortoiliac aneurysms applied a selective approach in deciding whether or not to embolise the IIA; Bharwani et al 22 and Farahmand et al 21 only included cases without coil embolisation in which attempted embolisation had technically failed or in which the IIA had been covered inadvertently. The group from the University of Wisconsin presented two reports on patients with and without coil embolisation, 24,25 but no reasons were provided for their decision whether or not to perform concomitant IIA embolisation. Wyers et al 23 decided not to embolise the IIA if a sealing zone of at least 5 mm was present in the most distal part of the CIA.…”
Section: Discussionmentioning
confidence: 99%
“…IIA-associated endoleaks (%) Lee C 2000 18 18 9 9 7.3 nr b 0 (0) Karch 2000 19 9 0 9 13.4 nr b 0 (0) Rhee 2002 15 6 0 6 4.7 nr b 0 (0) Weyers 2002 25 the retrospective design of our study, which might have caused relative underreporting in general. However, we consider specific questions with focus on pelvic ischaemia part of follow-up routine.…”
Section: Plannedmentioning
confidence: 97%
See 1 more Smart Citation
“…[2][3][4] Preoperative embolization of IIA is recommended to prevent type II endoleak although some report satisfactory outcomes without embolization. [5][6][7] Transcatheter embolization of IIA in patients with iliac aneurysms is usually accomplished with little morbidity. Factors that may influence technical success include the length of the CIA with associated aneurysm, tortuosity of the iliac arteries, coexisting IIA aneurysm, or stenosis.…”
Section: Case Reportmentioning
confidence: 99%
“…Conflicting reports have shown that the origin of the hypogastric artery can be covered with impunity in the setting of endovascular aortoiliac repair, 15 or complications can be seen in up to 40% of patients undergoing acute coverage or embolization of patent hypogastric arteries. 16 In response to the initial description of the endoconduit, Ysa et al 17 appropriately inquired whether back-bleeding from a patent hypogastric artery after controlled rupture of the iliac artery is of concern.…”
Section: Endoconduitmentioning
confidence: 99%